2022
DOI: 10.1021/acs.est.2c06471
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Polycyclic Aromatic Hydrocarbons Induce Immunosuppression in THP-1 Macrophages Characterized by Disrupted Amino Acid Metabolism

Abstract: Frequent chlorinated polycyclic aromatic hydrocarbon (Cl-PAH) occurrence in environmental samples and emerging detection in human serum have warned of their underestimated risks. Studies showed that some Cl-PAHs exhibit dioxin-like properties, implying immunotoxic potential but lacking direct evidence and specific mechanisms. Here, we integrated a high-content screening (HCS) system and high-resolution mass spectrometry to investigate the immune dysfunction and metabolic disruption induced by Cl-PAHs and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
2
10
1
Order By: Relevance
“…This study is supported by others showing that PM exposure from air pollution causes systemic inflammation [16] and the release of cytokines IL-6 and IL-8 in human bronchial epithelial cells and alveolar macrophages [17]. In addition, PAH exposures also hyperstimulate maternal immune cells in mouse models and exert a cytotoxic effect on human-derived macrophages [18,19].…”
Section: Inflammation From Wildfire Smoke Exposuresupporting
confidence: 82%
See 1 more Smart Citation
“…This study is supported by others showing that PM exposure from air pollution causes systemic inflammation [16] and the release of cytokines IL-6 and IL-8 in human bronchial epithelial cells and alveolar macrophages [17]. In addition, PAH exposures also hyperstimulate maternal immune cells in mouse models and exert a cytotoxic effect on human-derived macrophages [18,19].…”
Section: Inflammation From Wildfire Smoke Exposuresupporting
confidence: 82%
“…These findings provide the first evidence that wildfire smoke exposure in pregnancy may dysregulate placental immune status, particularly with exposures earlier in pregnancy. These results are concerning and build on previous examples that have shown chemical components of wildfire smoke such as polycyclic aromatic hydrocarbons (PAHs) to act as contribute to an immunosuppressive effect on macrophages [19]. There is little data on the composition of wildfires from distinct wildfire events.…”
Section: Discussionmentioning
confidence: 56%
“…172 For XPAHs, prior research has revealed that specific XPAHs (9-chloroanthracene and 2,7-dichlorofluorene) could instigate immune dysfunction and metabolic disruption in THP-1 macrophages, with clear evidence of immunosuppression and complex modifications in the multicytokine/chemokine network. 173 As for OPAHs, studies on cellular effects of OPAHs in PM 2.5 report diminished cell viability, increased nitric oxide, and escalated production of tumor necrosis factor α (TNF-α) and interleukin 6 (IL-6). 174 16 Furthermore, benzanthrone has been found to exert immunomodulatory effects in mice via oxidative stress and inflammatory mediators.…”
Section: Derivatives and Potential Exposure Biomarkersmentioning
confidence: 99%
“…Mainly originating from incomplete combustion and chemical synthesis, they are frequently detected in various environmental and food sources, including seafood, rice, air, soils, and surface water . Research has revealed higher levels of Cl-Ants in indoor cockroaches compared to indoor dust, signifying a substantial bioaccumulation. , Moreover, recent findings have confirmed the presence of Cl-Ants in human serum, with higher levels observed in occupational exposures compared to environmental exposures. , However, research into the toxicity of Cl-Ants was limited, with individual studies indicating potential health risks such as DNA damage in rat hepatoma cells and immunosuppression in macrophages . The current majority of research on PAHs/Cl-PAHs is predominantly focused on the AhR pathway.…”
Section: Introductionmentioning
confidence: 99%